Questionable Utility of the Eccentric Utilization Ratio in Relation to the Performance of Volleyball Players - Žiga Kozinc (MDPI AG, 2021)
The difference between squat jump (SJ) and countermovement jump (CMJ), termed eccentric utilization ratio (EUR), is frequently suggested as an outcome that can be used in athletic training design. Unlike performance in SJ and CMJ, which is associated with sports performance, the association between EUR and sports performance is almost unexplored. This study aimed to investigate whether EUR is associated with performance in approach jump, linear sprint and change of direction (CoD) tasks in volleyball players. Forty-five male volleyball players performed SJ, CMJ, 25 m linear sprint, approach jump and two CoD tasks (505 test and modified T-test). EUR was calculated based on jump height, peak power, peak force and average power. SJ and CMJ variables showed moderate to high correlation with approach jump performance (r = 0.42–0.70), small correlation with modified T-test (r = 0.33–0.40) and small to moderate correlation with sprint time (r = 0.35–0.49). EUR showed only small associations with performance variables (r = 0.31–0.34). In all linear regression models with performance outcomes as dependent variables, the CMJ height was always the only statistically significant predictor. Our results support the recent arguments that the EUR offers limited insight into the neuromuscular capabilities of athletes.